2008
DOI: 10.1002/elan.200704063
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue Dispersed Sphere Catalytic Labels for Amplified Electronic Detection of DNA

Abstract: A highly sensitive electrochemical DNA hybridization assay using Prussian blue (PB)-modified polymeric spheres as the oligonculeotide labeling tag is described. The sandwich assay relies on a secondary nucleic-acid probe functionalized with polystyrene beads loaded with numerous Prussian blue nanoparticles. The very strong catalytic activity of the captured PB 'artificial peroxidase' tag towards the reduction of hydrogen peroxide, along with the encapsulation of numerous catalytic particles onto polymeric bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…3,16 In previous studies, they have been demonstrated to be applicable to the sensing of hydrogen peroxide at a low applied potential, allowing the integration of oxidase enzymes while reducing other electrochemical interferents. 3,15,25,[29][30][31][32][33][34][35][36][37][38] Other Prussian blue-based biosensors, such as glucose, 25,[39][40][41][42][43][44][45][46][47][48][49][50][51] pH, 22 lactate, 38,[52][53][54] antigen, 55 cholesterol, 56,57 DNA, 24,54,58 glycan, 59 antihypertensive drug, 23 carcinoma antigen, 60 ion, 24,61 uric acid, 62 ascorbic acid, 63 and nicotinamide adenine dinucleotide (NADH) [64]…”
Section: Introductionmentioning
confidence: 99%
“…3,16 In previous studies, they have been demonstrated to be applicable to the sensing of hydrogen peroxide at a low applied potential, allowing the integration of oxidase enzymes while reducing other electrochemical interferents. 3,15,25,[29][30][31][32][33][34][35][36][37][38] Other Prussian blue-based biosensors, such as glucose, 25,[39][40][41][42][43][44][45][46][47][48][49][50][51] pH, 22 lactate, 38,[52][53][54] antigen, 55 cholesterol, 56,57 DNA, 24,54,58 glycan, 59 antihypertensive drug, 23 carcinoma antigen, 60 ion, 24,61 uric acid, 62 ascorbic acid, 63 and nicotinamide adenine dinucleotide (NADH) [64]…”
Section: Introductionmentioning
confidence: 99%
“…27 However, PB/CTAB films did not provide sharp current responses in the presence of Na + because the channel was not wide enough to allow hydrated Na + to enter into the matrix. 28 nanomaterials such as carbon nanotubes, 11 magnetite, 29 polystyrene spheres, 30 CdS, 31 Au, 32,33 or Pt. 34 The introduction of nanostructured hybrid materials increases the surface to volume ratio and the surface activity, which leads to a wider pH range, improved electrochemical stability, and excellent electrochemical response.…”
Section: Introductionmentioning
confidence: 99%
“…Prussian blue, a dye with long history, has been widely used in many fields such as optical physics, magnetism, and electrochemical for its excellent properties. [1][2][3] Prussian blue, certificated by Food and Drug Administration for treating thallium radiation poisoning, also has been used as a conventional drug in hospital. 4 In recent years, Prussian blue nanoparticles (PBNPs) have attracted much attention due to their excellent photothermal and imaging abilities and have been widely used in biomedical fields such as biosensor, cancer photothermal therapy, and magnetic resonance (MR) imaging.…”
Section: Introductionmentioning
confidence: 99%